Water injection system design for six stroke engine - Muhamad Nurzami, Ab Sota (2012)
The engine for automobile is developed rapidly from each year as to increase the performance and able to decrease the fuel consumption. Various method and concept had be proposed previously based on mechanism, new attachments and material usage for the engine. This thesis is about the water injection system design for currently new six stroke engine as one of development engine method. The objectives of this project are to design new water injection system and find suitable components that compatible with this system. This project describes about process for design and fabricated the water injection system based on selected concept design. Some of concept design were proposed earlier and compared together. Then, the concept with the good mechanism and able to built was selected and designed using Solidwork software. The concept was chosen by considering the capability to operate the system, functionality, area usage and material or components chosen. This concept is generated from the fuel injection system for diesel engine where the fuel injection was controlled through fuel pump and pumping operation driven by rotation of camshaft. Hence, the similar system was presented here by some component modification in order to produce the six stroke engine. The complete manufactured water injection system was analyze by testing them with experimental as to achieve best result. The fabrication process was conducted following the dimension of modeling design and some modification to the existing component. The complete water injection system was fabricated successfully and several analysis tests have been conducted to measure the capability of our system. Two testing have been made to determine the performance of water pump with different pressure and amount of water injected by water injector. The result showed that the injections pump produce different pressure with time duration and plunger pump compression. The water injector was modified to obtain the suitable opening pressure to inject specific amount of water into combustion chamber.